Design and Implementation of the Front-End E-Learning Website for the Banda Aceh Tekkomdik Laboratory - Sari, Anisa Puspita; Sarif, Muhammad Irfan (Cattleya Darmaya Fortuna, 2023)
UPTD Balai TEKKOMDIK Banda Aceh itself is the Task Implementation Unit of the Banda Aceh City Education Service. The Center for Educational Technology and Communication (TEKKOMDIK) has tasks, one of which is developing information technology in Banda Aceh City education units in elementary and middle school environments. At UPTD TEKKOMDIK Hall there are several school services such as the E-Learning application. E-Learning Application Services are still less effective to use and are still not responsive. Therefore, in the design and implementation of the front-end E-learning website for UPTD Balai TEKKOMDIK Banda Aceh, it is necessary to develop an E-Learning application with display features that can make things easier and of course responsive. The development of the Front-End section aims to facilitate the teaching and learning display process, including displaying Admin features for user management such as teachers and students, classes, subjects, then there is also a display of features for students such as learning media, for example materials, assignments, and direct chat. Apart from the several display features that have been mentioned, there are also other display features such as display of school service features, school information, school profile, learning media and educational channels which are useful for providing information regarding assignments and materials.